MENTORING LEARNING BAGI ANAK-ANAK DALAM MENGHAFAL SURAH AL-QARIAH SESUAI DENGAN MAKHARIJUL HURUF DENGAN METODE WAFA DI DUSUN BOGELAN - Ulfah Susilawati, Nida Ulya Hakim, Siti Khoirul Khafidhoh, Yunissa Wahyuni, Fitria Maharani (ALKADIMAT, 2024)
Education is the main provision for humans to be able to explore their talents and potential. Education is one of the things that can help someone to change their life, change someone from not knowing to knowing, from not being able to being able to and from being bad to being good. The mentoring learning program (assistance in learning) is a form of learning carried out in a smaller scope. Reading is the basis of knowledge. However, Islamic religious education and the Koran in Indonesia, which is one of the important pillars of developing the civilization of Indonesian society, still receives little attention. In the implementation of Tajwid Al-Qur’an learning, students will be taught or guided by Tajwid supervisors in reading the Al-Qur’an by paying attention to makhraj, tajwid, and waqf signs in accordance with the rules and regulations for reading the Al-Qur’an. The research approach used is a qualitative approach. Based on the results obtained, based on the mentoring and learning process in applying the wafa method to help the children of Bogelan Hamlet, Tegalsari Village, Candimulya District, Magelang in memorizing Surah Al-Qariah according to the makharijul letters, it is quite effective.